International commercial courts : the future of transnational adjudication / edited by Stavros Brekoulakis, Queen Mary University of London, Georgios Dimitropoulos, Hamad Bin Khalifa University. - Brekoulakis, Stavros L.; Dimitropoulos, Georgios, 1984- (Studies on international courts and tribunals., 2022)
The book offers a comprehensive analysis of the role, importance and place of international commercial courts in the field of international adjudication from a comparative perspective. In a time where scholarly and academic debates revolve around the issues of the role of law in the post-globalization era, the new international commercial courts seem to be in the position to bridge concerns regarding diminished sovereignty, on the one hand, and the necessity of globalizing dispute resolution, on the other. International commercial courts thus present themselves as the paradigm for the future of adjudication.